Berberis aristata Ameliorates Testicular Toxicity Induced by Combination of First-Line Tuberculosis Drugs (Rifampicin + Isoniazid + Pyrazinamide) in Normal Wistar Rats. (4th July 2019) - Sharma, Radhika; Goyal, Neha; Singla, Mandakini; Sharma, Vijay Lakshmi
ABSTRACT: First-line antituberculosis drugs, namely, isoniazid (INH), rifampicin (RIF), and pyrazinamide (PZA), contribute to diverse pathological complications. Testicular toxicity is one such complication. Berberis aristata DC is an herb with potentially curative characteristics. The aim of this study was to test whether extract of Berberis aristata DC (Berberidaceae) has curing potential against testicular toxicity. Characterization of extract was done using ultra-performance liquid chromatography along with acute toxicity testing. Antioxidant activity of extract was checked by DPPH inhibition assay and H2 O2 scavenging assay. Rats were dosed once daily for 28 days in groups: control group (saline), toxicant group (30.85 mg/kg body weight INH + 61.7 mg/kg body weight RIF + 132.65 mg/kg body weight PZA), treatment groups (TB drugs + 150/300 mg/kg body weight extract) and standard group (TB drugs +100 mg/kg body weight silymarin). Spectrophotometric evaluations of lipid peroxidation (LPO), reduced glutathione (GSH), superoxide dismutase (SOD), glutathione-S-transferase (GST), and catalase (CAT) content in testes were done using standard protocols. DNA fragmentation and histopathological studies were performed to check the damage at the cellular level. Acute toxicity studies revealed LD50 > 5 g/Kg body weight of B. aristata extract. IC50 for DPPH free-radical scavenging activity and H2 O2 scavenging assay were 44.78 µg/mL and 85.28 µg/mL, respectively. Results revealed significant increase in thiobarbituric acid reactive substances, decrease in glutathione and different antioxidants levels, DNA fragmentation pattern, and changes in histology in toxicant group. All the changes were absent in high-dose (300 mg/kg body weight) extract treatment group. This work proved that B. aristata extract has protective efficacy against testicular damage caused by anti-TB drugs.